Efficacy of mitoxantrone-based salvage therapies in relapsed or refractory acute myeloid leukemia in the Mayo Clinic Cancer Center: Analysis of survival after 'CLAG-M' vs. 'MEC'. (March 2020) - Scheckel, Caleb J; Meyer, Megan; Betcher, Jeffrey Alan; Al-Kali, Aref; Foran, James; Palmer, Jeanne
Highlights: We compared CLAG-M and MEC in relapsed and refractory AML. Response rates were 61 % for CLAG-M and 56 % for MEC. No significant differences in overall survival were seen between the 2 regimens. Trends towards improved survival in those treated with MEC then ASCT were noted. Superior survival may occur in patients with late relapse treated with MEC then ASCT. Abstract: Salvage therapy regimens for refractory and relapsed AML include mitoxantrone, etoposide, and cytarabine (MEC) and cladribine, cytarabine, filgrastim, and mitoxantrone (CLAG-M). We analyzed patients receiving either CLAG-M or MEC as salvage therapy for RR-AML between 09/01/2009-12/31/2017. Of 150 patients with RR-AML, 34 patients received CLAG-M and 116 MEC. CR/CRi rates for CLAG-M and MEC were 61.3 % (19/31) and 55.6 % (60/108). Median OS was 9.5 months for CLAG-M and 10.0 months for MEC (HR = 0.88, 95 %CI = 0.54–1.41, p = 0.59). 76 patients proceeded to ASCT following salvage therapy. Median OS after ASCT was 13.0 months for CLAG-M and 31.0 months for MEC (HR = 1.76, 95 %CI = 0.87–3.56, p = 0.12). Among those with late relapse and ASCT, median OS was 9.0 and 48.0 months for CLAG-M and MEC, respectively (HR = 17.6, 95 %CI = 1.57–198, p < 0.001). There were no significant differences in outcome between CLAG-M vs. MEC regardless of transplant status. There was a significant improvement in survival in patients with late relapse treated with MEC who proceeded to ASCT.